THE EFFECT OF MANGOSTEEN (GARCINIA MANGOSTANA) PERICARP EXTRACT ON RETINOBLASTOMA CELL CULTURE PROLIFERATION - Fariz Nufiarwan; Lely Retno Wulandari (Indonesian Vitreoretinal Society, 2019)
Introduction: To determine the effect of mangosteen (Garcinia mangostana) pericarp extracts on retinoblastoma cell culture proliferation. Methods: This study is a true experimental in vitro design with pre and post-test control group design. Research using retinoblastoma cell culture exposed by mangosteen pericarp extract (Garcinia mangostana) at a dose of 10 µg/ml, 20 µg/ml, and 40 µg/ml. Result: This study used retinoblastoma cell line cultures were obtained from the American Type Culture Collection (ATCC) 10801 University Boulevard Manassas, VA 20110 USA. The samples were divided into 4 groups: control group and 3 groups treated with doses of 10 µg/ml, 20 µg/ml and 40 µg/ml and then incubated for 48 hours, and then examined using MTT Cell Proliferation Assay. Group 1 (10 µg/ml) obtained a decrease of 151.8%, group 2 (20 µg/ml) of 134.6% and group 3 (40 µg/ml) of 134.36%. Conclusion: Mangosteen pericarp extract (Garcinia mangostana) can reduce retinoblastoma culture cell proliferation.